Revenge, Hatred, Love, and Regret: The Use of Narrative Empathy in a Regional Purana - Brussel, Noor van (Religions of South Asia, 2016)
This article analyses the character of the demon found in the Sanskrit Bhadrakalimahatmya. This regional Puranic text, pertaining to the narrative tradition of the Darikavadham from Kerala, adopts a specific stance with regard to its main antagonist, the asura king Darika. While the Bhadrakalimahatmya eagerly engages with various Mahapuranas such as the Linga and the Markandeya, the demon that it depicts contrasts with the rather rigid image set out by his counterparts in those texts. Instead, the demon's character is carefully drawn and led through an array of emotional states in a way that tempts the audience to empathize. In this article, I explore this strategic empathy. Perusing the narratives of the Bhadrakalimahatmya, I identify passages that are activated by strategies of affect and show how they construct the character of the demon. In the second part of the article, I attempt to unravel the motives for this alternative view of the demon, relying on frameworks stemming from contemporary studies of narrative empathy and classical Indian theories of aesthetics.